Aesop's fables adaptation: an alternative for fostering values, oral production and listening comprehension - Pedraza Hernández, Blanca Ximena; Castiblanco Gil, Heidy Liliana (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article aims at presenting the experiences acquired from the project titled “Aesop’s Fables Adaptation: An Alternative for Fostering Values, Oral Production and Listening Comprehension”, carried out at a public school in Tunja with fourth graders. The project related to the adaptation of Aesop´s fables, which were included in the school´s curriculum topics and implemented through different workshops. This was done in order to develop values awareness and English skills. Throughout this project, most of the students participated, were very attentive class after class, and enjoyed the activities. The students began to use the vocabulary they learnt from the fables for communicative purposes. In the same way, students were aware of moral aspects, the implicit values in each story, and the fables’ importance in their own lives